ORIENTASI POLITIK DAN BENTUK KETERLIBATAN PAGUYUBAN MAHASISWA BENGKALIS DI PEKANBARU PADA PILKADA BENGKALIS TAHUN 2015 - Muhammad Wira Kurniawan; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Direct election of Head of Region is one of democracy change, where post reformation gives freedom and wide autonomy to region, which during the New Order period for 32 years grips Indonesian society. Paguyuban Mahasiswa which in this case is known by another name of Student organization is a place for students to pour their critical mind to make a better organization or paguyuban. The role of Paguyuban Students in the success of Pilkada is very important because in the process of lecturing students are also taught about the life of the state and government. In the elections of Bengkalis in 2015, there is a difference of support and attitude from every Paguyuban Bengkalis Student Sub-district level Group in Pekanbaru. The method used in this research is descriptive method with qualitative approach. The type of research data is primary data and secondary data. Data collection techniques in this study are documentation and interviews. Technical data analysis used is descriptive qualitative data analysis. The results of this study indicate that the political orientation of Bengkalis Student Society has 3 (three) types, that is First, the cognitive orientation is the knowledge of Pilkada, the figure of the future Leader. Second, the orientation of affection is the feelings that concern the problem of emotional bonds possessed by individuals against prospective Leaders. Third, an evaluative orientation which means a combination of knowledge of the candidate and the similarity of the area of residence, tribe, gamma, race, and other similarities. The form of involvement of Bengkalis Student Society in Pilkada is involved in pilkada activities, lobbying process, organizational activity, seeking connection (contacting), and also intervention and intimidation. Furthermore, there is a relationship between political orientation with the form of involvement of Bengkalis Student Society in Pilkada 2015. Keywords: Political Orientation, Forms of Involvement, Student Association and Regional Head Election